PROTECTIVE EFFECTS OF ETHYL ACETATE EXTRACTION FROM GASTRODIA ELATA BLUME ON BLOOD-BRAIN BARRIER IN FOCAL CEREBRAL ISCHEMIA REPERFUSION - He, Fangyan; Duan, Xiaohua; Dai, Rong; Wang, Wei; Yang, Cui; Lin, Qing (African Journal of Traditional, Complementary and Alternative Medicines, 2016)
Background: Damage of the blood brain barrier (BBB) during the process of cerebral ischemic injury is a key factor which influences the therapeutic efficacy to the cerebral ischemic injury. The present study was designed to verify the mechanisms underlying the protective effects of the ethyl acetate (EtOAc) extraction from Gastrodia elata Blume (GEB) on the BBB by developing a model of cerebral ischemia-reperfusion in rats. Material and methods: MCAO/R model in rats was developed through a thread embolism method. The neurological scales, the moisture and the evans blue (EB) contents of brains were detected. Meanwhile, the release of nitric oxide (NO) and activities of NO synthase (NOS) in brain tissues were measured. Western blotting analyses were also performed to assess the protein expressions of AQP-4, Occludin and Claudin-5 in brain tissue. Result: After rats were pretreated with different concentrations of EtOAc extractions from GEB, the neurologic scores, the EB contents in the brain tissues and the moisture of the brains were significantly decreased. Meanwhile, the release of NO, the activities of nNOS and iNOS were notably inhibited. Furthemore, the protein expression of AQP-4 was markedly decreased, but the protein expressions of Claudin-5 and Occludin were significantly increased. Conclusion: the EtOAc extracts of GEB may decrease the permeability of BBB when focal cerebral ischemia occurs. The inhibition of the NOS pathways, the attenuation of the protein expression of AQP-4 and the enhancement of the expressions of the tight junction proteins may contribute to the protective effects of the EtOAc extracts from GEB on BBB.